LINGUOCOGNITIVE FEATURES OF CONTEXTUAL ANTONYMS IN THE ENGLISH AND UZBEK LANGUAGES - Usmonov Shohsulton, (TADQIQOTLAR, 2026)
Abstract:  The  present  article  investigates  the  linguocognitive  features  of contextual  antonyms  in  the  English  and  Uzbek  languages  from  a  comparative  and interdisciplinary perspective. Unlike conventional lexical antonyms, which are fixed and systemically encoded in the language, contextual antonyms emerge dynamically within  discourse  as  a  result  of  cognitive  operations,  pragmatic  intentions,  and situational  constraints.  The  study  is  grounded  in  the  theoretical  frameworks  of cognitive linguistics, linguoculturology, and discourse analysis, viewing language as a reflection  of  human  conceptualization  and  mental  categorization  of  reality.  In  this regard, contextual antonymy is interpreted not merely as a semantic opposition, but as a cognitively motivated mechanism through which speakers conceptualize contrast, evaluation, and categorization in context. The research aims to identify the cognitive principles  that  underlie  the  formation  and  interpretation  of  contextual  antonyms  in English and Uzbek, and to reveal both universal and language-specific features of this phenomenon.  Particular  attention  is  paid  to  such  linguocognitive  mechanisms  as conceptual  opposition,  profiling  and  backgrounding,  metaphorical  and  metonymic mapping, scalar evaluation, and frame-based interpretation. The analysis demonstrates that contextual antonyms are often activated through shared background knowledge, cultural  models,  and  pragmatic  inferences,  rather  than  through  direct  lexical opposition.  As  a  result,  the  recognition  of  antonymic  relations  depends  heavily  on discourse context and the interlocutors’ cognitive competence.